ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADI SAWAH DI KECAMATAN SENYERANG KABUPATEN TANJUNG JABUNG BARAT - Oktari Ulma, Riri; Ningsih, Rozaina (JALOW | Journal of Agribusiness and Local Wisdom, 2019)
This research aims to determine the factors that influence the production of lowland rice farming. This research was carried out in Senyerang Subdistrict, Tanjung Jabung Barat District. The data used in the form of primary data data obtained by direct interviews with farmers using a questionnaire while secondary data obtained from related agencies, the internet and literature. Sampling is done purposively (purposive) then 48 samples are obtained. Analysis of the data used is multiple linear regression analysis. Based on the results of multiple linear regression shows that the factors that influence the production of lowland rice are land area (X1), seeds (X2), urea fertilizer (X3), NPK fertilizer (X4), SP36 fertilizer (X5), labor (X6) and pesticides (X7). The factors that have a positive influence are land area (X1), seeds (X2), urea fertilizer (X3), labor (X6). Increasing these variables will increase rice production in the research area, while increasing NPK fertilizer (X4), SP36 fertilizer (X5), and pesticides (X7) will reduce the production of lowland rice in the study area because of its negative effect.